(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The most pertinent problem post pandemic is about the risk perception in the minds of consumers specially pertaining to online purchase of durables like electronics. This study throws light on this significant issue. Primary data responses were collected online via structured questionnaire from 120 consumers Pan India to understand the consumer; s risk perception regarding their online purchase intentions. Multiple regression was administered to identify the issues. On the basis of analysis, it was found that product risk as well as risk of losing money and other financial details significantly impacts the consumer’s perception. The study paves a way for understanding comsumer’s intentions and will help marketers design better strategies for increasing online purchase of electronics.